A clinical study of cutaneous manifestations in neonates at a tertiary health care center - Sneha, M.; Sadagopan, Kumaravel; D., Vaishnavi (International Journal of Research in Dermatology, 2021)
Background: Cutaneous alterations are commonly seen in neonates as a normal process of adaptation to the external air environment after birth. It is good to know about transient skin lesions in infants to distinguish them from other conditions that prevent unwanted neonate therapy. Parents should be confident of the excellent prognosis of these manifestations of the skin. The aim of the study was to determine the patterns of cutaneous manifestations occurring among the newborn. Methods: This prospective study was conducted in the newborn with at-least one cutaneous manifestation. A detailed history of the neonates and mother was collected using pre-designed proforma. Results: Of 100 neonates, 52 were males, 48 were females, of these, 85 were born at term, 10 were preterm, and 5 were post-term. Mongolian spot was seen in lumbosacral, buttocks and extremities in 80 (80%) neonates, vernix caseosa in 20 (20%) neonates. Milia in 14 (14%) neonates, eczematous eruption in 30 (12.5%). Conclusions: This neonatal skin research has provided details on normal variants occurs during the neonatal phase. It is necessary to know that most newborn skin lesions are temporary and do not require any treatment.